Design for Random Response of Structures Subject to Rhythmic Crowd Loading - Jing-Kun Dong; Mao Ye (Buildings, 2023)
Overall, this paper provides a comprehensive approach for designing structures subject to rhythmic crowd loading. By considering the randomness of the load model and structural response, the design method provides a more realistic evaluation of the structure’s performance. The establishment of links between the deterministic individual loading and the random crowd loading simplifies the calculation process and makes it more practical for real-world applications. The use of reduction factors based on experimentally determined standard deviations ensures that the design method provides a lower bound for the expected response of the structure. The consideration of the involvement of an infinite number of people in the reduction factors adds an additional level of conservatism to the design, further ensuring the safety of the structure. The examples provided illustrate the effectiveness of the design method in evaluating the maximum displacements and accelerations of a floor structure subjected to rhythmic crowd loading. Overall, the paper provides a valuable contribution to the field of structural engineering by providing a practical and realistic approach for designing structures subject to rhythmic crowd loading.